1998
DOI: 10.1111/j.1439-0388.1998.tb00345.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of selection on reaction to stress in mice V. The effect of starvation and glutathione injection on the activity of N‐acetyl‐beta‐glucosaminidase and the level of glutathione in the liver

Abstract: Summary The experiment was conducted on 40 6‐week‐old mice selected for a high rate of body weight gain and 40 unselected controls. Model stressors were used: starvation for 24 h, injection of glutathione and both stressors jointly. Measurements were made of N‐acetyl‐beta‐glucosaminidase (NAGL) activity and the level of non‐protein sulfhydryl groups in the liver. Starvation, glutathione injection and starvation with glutathione injection jointly caused an increase of NAGL activity, which was more marked in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…This experiment continued previous studies ( Witek 1998 ; Koątaj et al . 1992 , 1995, 1996; Rysińska et al .…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…This experiment continued previous studies ( Witek 1998 ; Koątaj et al . 1992 , 1995, 1996; Rysińska et al .…”
Section: Introductionsupporting
confidence: 91%
“…The earlier studies ( Ko&aogon,taj et al . 1995 , 1996; Witek & Ko&aogon,taj 1998) showed that selection for a high rate of body weight gain can change the biochemical reactivity of an organism in connection with damaging environmental factors. The conclusions are similarto those that can be inferred from the papers of Gunselt et al .…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier studies revealed that the activity of the degradation system of the lysosomal compartment is a significant factor maintaining the animal cell in the state of dynamic homeostasis, as well as an important indicator of stress reactivity. Observations conducted on pigs (KOŁĄTAJ et al, 1996), cattle (KOŁĄTAJ et al, 1998), sheep (KOŁĄTAJ et al, 2002 as also on mice (JÓŹWIK et al, 2003 a b;LANKOFF and KOŁĄTAJ, 2001;WITEK and KOŁĄTAJ, 1998, 2001), rabbits (KONECKA et al, 2002 and quail confirmed this hypothesis. The data obtained from them indicate that the stress factors, employed in these studies, caused the significant changes in the reactivity of the animal cell lysosomal system.…”
Section: Discussionmentioning
confidence: 87%
“…In connection with these data, it seemed interesting to estimate the changes of the activity of some model lysosomal enzymes in the blood plasma of young bulls and heifers maintained in farm conditions, fed normally and starved for a short period. Fasting or restriction of food are a specific types of stress burden, which appears quite often in domestic animals (OHSHITA et al, 1986;WITEK and KOŁĄTAJ, 1998). The aim of this study was to determine the influence of starvation and sex on the activity of some lysosomal enzymes in young cattle.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained suggest that selected mice, receiving both types of diets, have as a rule higher enzyme activity than unselected control animals. The studies of Witek and Kołątaj (1998) and Kołątaj et al (1998) indicate that the lysosomal system is significantly connected with homeostasis. Homeostatic disturbances caused by prolonged selection may also be observed in the activity of non‐lysosomal enzymes ( Kołątaj et al 1995, 1996).…”
Section: Discussionmentioning
confidence: 97%